(untitled) (Journal of the College of Basic Education, 2024)
The current research aims to identify the effectiveness of the six-dimensional strategy in developing metacognitive skills among students of the Art Education Department in the subject of art criticism. The researcher used an experimental design with partial control for two equal groups (experimental and control) in some variables, and with a post-test (metacognition scale). The research sample was intentionally chosen from fourth-year students - Department of Art Education - College of Fine Arts - University of Baghdad - for the academic year 2023. /2024, and by simple random drawing, Division (D) represented the experimental group that studied according to the six-dimensional strategy with (20) male and female students, Section (F) was the control group that studied in the usual way with (20) male and female students. The research tool was determined by a measure of metacognitive skills, and the validity and reliability of the tool was confirmed. The researcher took care to provide internal and external safety for the experiment, and the researcher prepared (14) teaching plans, including (7) plans for the students of the experimental group and (7) plans for the students of the control group. After completing the experiment, a metacognitive skills scale test was conducted After obtaining the data and processing it using statistical methods represented by the Mann-Whitney test for two independent samples of equal numbers, the results were obtained, and in light of them, the researcher concluded the following: The students of the experimental group who studied according to the six-dimensional strategy outperformed the students of the control group who studied according to the regular method in the measure of metacognitive skills. The researcher recommended emphasizing the use of the six-dimensional strategy as better than the usual method in developing metacognitive skills for fourth-stage female students.